Pemertahanan Bahasa Tado di Kecamatan Lindu Kabupaten Sigi Sebagai Bentuk Pelestarian Pendidikan Bahasa Daerah - Nasim Taha; Al- Afandi (Jurnal Paedagogy, 2022)
The purpose of this research is to describe the efforts to maintain the Tado language in Lindu District, Sigi Regency as a form of preserving regional language education. This research method uses a descriptive qualitative approach. The data sources of this research are native speakers who use the Tado language with data collection techniques carried out are interviews, observation, and documentation. The data analysis technique used descriptive analysis. The results of this study indicate that the maintenance of the Tado language in Lindu District, Sigi Regency cannot be separated from the role of the community, namely with various creative efforts to maintain the Tado language, including carrying out cultural activities and also producing works using the Tado language with publish it on social media, the government also has a role in maintaining tado language by including tado language in local content subjects at school.